Preparation method of molecular sieve and prepared molecular sieve

By using the ultra-gravity aging crystallization integrated device during the preparation of molecular sieve, the integration of aging and crystallization is achieved, solving the problems of complex operation and low efficiency in the prior art, and improving the preparation efficiency and product performance.

CN119774635APending Publication Date: 2025-04-08CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311296753.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-08
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, it is difficult to integrate the aging and crystallization process during the preparation of molecular sieve. Each operating unit is carried out independently, and the synthesis process is complex, resulting in low efficiency and high cost.

Method used

The ultra-gravity aging crystallization integrated device is used to simplify the synthesis of molecular sieve, and the aging crystallization is directly performed after premixing in the device, so as to achieve the integration of aging crystallization.

Benefits of technology

The industrial operation steps are simplified, the preparation efficiency of molecular sieves is improved, the cost is reduced, and the prepared molecular sieves have good morphology and are suitable for applications such as butene cracking reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774635A_ABST
    Figure CN119774635A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a molecular sieve and the prepared molecular sieve. The preparation method comprises the following steps: preparing initial gel which comprises a silicon source, an aluminum source, a template T, water and an optional phosphorus source, feeding the initial gel into a supergravity aging crystallization integrated device for premixing circulation, then directly crystallizing, taking out of the device, and drying to prepare a molecular sieve; according to the crystallization, non-cyclic crystallization is directly carried out after premixing circulation in the supergravity aging and crystallization integrated device. According to the preparation method provided by the invention, in the preparation process of the molecular sieve, the synthesis of the molecular sieve is simplified by adopting a supergravity aging and crystallization integrated device, and the industrial operation steps are simplified.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a molecular sieve and the prepared molecular sieve, belonging to the technical field of molecular sieve synthesis. Background Art

[0002] Conventional molecular sieve synthesis requires two steps: aging and crystallization. The aging time is 4-48 hours and the crystallization time is 6-120 hours, which is time-consuming and leads to industrial problems such as low process efficiency, high cost and high material consumption. The molecular sieve preparation system is complex, the synthesis process is high temperature and pressure, and involves multiple processes such as premixing and crystallization, and each process has different process requirements.

[0003] CN201210287914.1 discloses a method for preparing a mesoporous zeolite molecular sieve, wherein tetraethyl orthosilicate is used as a silicon source, sodium aluminate is used as an aluminum source, and a bifunctional triammonium quaternary ammonium salt cationic surfactant is used as a template agent, and a mesoporous zeolite molecular sieve with microporous crystallized pore walls is prepared by a hydrothermal synthesis method under alkaline conditions. The quaternary ammonium salt surfactant used in the method produces micropores as a zeolite structure directing agent, and the aggregation between the long hydrophobic alkyl groups at both ends forms mesopores. The method effectively changes the amorphous pore wall structure of traditional mesoporous materials, making them have crystallized pore walls, greatly improving the acidity and hydrothermal stability of mesoporous materials, and the prepared mesoporous zeolite molecular sieve has a unique mesopore / micropore multiple pore structure, can avoid the defects of a single pore structure, improve mass transfer efficiency, and has a wide range of application prospects in macromolecular catalysis, adsorption and separation. CN201310020530.8 introduces a zeolite synthesis method, which uses a polar molecule, namely hexadecyltrimethylammonium bromide, to intercalate a layered silicate Na-kenyaite to obtain a Na-kenyaite-CTAB intercalation complex, and then uses tetraalkylammonium hydroxide as a template to synthesize a molecular sieve, and the product is subjected to a layer peeling treatment to obtain a thin sheet of molecular sieve crystals. The intercalation process expands the interlayer spacing and maintains a certain distance to avoid mutual fusion. During the crystallization process, the growth rate is controlled so that the molecular sieve can nucleate and grow along the layer of the layered material. After the reaction is completed, the template and polar molecules are removed. Finally, while the molecular sieve is obtained, the two-dimensional structure of the layered material is also retained, which greatly improves the accessibility of the macromolecular reactant and the active acid center and improves the reaction performance. CN200910072747.7 introduces a method for preparing a molecular sieve, which includes adding pre-crystallized seeds into a gel system for synthesizing nanomolecular sieves without a template, crystallizing at 160-180°C for 24 hours, cooling to room temperature, centrifuging the product, washing, drying, and calcining to obtain a molecular sieve without impurity crystal phase.

[0004] In the method described in the above patent, the aging and crystallization processes are not integrated, each operation unit is carried out independently, and ultra-gravity is not used, so the molecular sieve synthesis process is relatively complicated. Summary of the invention

[0005] In order to solve the problems in the prior art that it is difficult to integrate the aging and crystallization processes in the preparation of molecular sieves, each operation unit is carried out independently, and the synthesis process of the molecular sieve is relatively complicated, the present invention provides a new method for preparing molecular sieves and the prepared molecular sieves, wherein the preparation method adopts an ultra-gravity aging and crystallization integrated device in the molecular sieve preparation process, simplifies the molecular sieve synthesis, and simplifies the industrial operation steps.

[0006] The first aspect of the present invention provides a method for preparing a molecular sieve, comprising the following steps:

[0007] Prepare an initial gel, including a silicon source, an aluminum source, a template T and water, and an optional phosphorus source, send it into a high-gravity aging crystallization integrated device for premixing and circulation, then directly crystallize it, and dry it after leaving the device to prepare a molecular sieve;

[0008] The crystallization is directly carried out as non-cyclic crystallization after premixing cycle in the integrated device for high gravity aging crystallization.

[0009] Furthermore, the ultra-gravity aging crystallization integrated device includes a feeding system, a reaction system, and a discharging system.

[0010] Furthermore, the initial gel is fed through a feeding system of the integrated device for high gravity aging and crystallization, and then undergoes premixing cycle reaction and crystallization in the reaction system in sequence, and then exits the device through a discharging system.

[0011] Further, the template agent T is at least one of tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetramethylammonium bromide, tetraethylammonium bromide, tetrabutylammonium bromide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, n-propylamine, n-butylamine, n-hexylamine, methylamine, ethylamine, ethylenediamine, diethanolamine, hexamethylene diisocyanate, hexamethylenediamine, hexamethylenetetramine and its derivatives (urotropine and its derivatives). The silicon source is at least one of silica sol, tetraethyl orthosilicate, and silicate, and the aluminum source is at least one of aluminum sulfate, aluminum isopropoxide, and aluminate. The water can be deionized water. The phosphorus source is at least one of phosphoric acid or phosphate.

[0012] Furthermore, the molar ratio of the silicon source, aluminum source, template T, phosphorus source and water is H2O / SiO2=10-500; Si / Al=20-∞, T / SiO2=0.01-20, P / SiO2=0-50.

[0013] Furthermore, when the initial gel is fed through the ultra-gravity aging crystallization integrated device, the feeding rate is 10-2000 ml / min, preferably 15-300 ml / min.

[0014] Furthermore, during the premixing cycle in which the initial gel is fed into the reaction system through the integrated device for high-gravity aging and crystallization, the high-gravity rotation speed is maintained at 1000-2500 rpm, preferably 1200-2000 rpm, for 5 min-48 h.

[0015] Furthermore, the crystallization conditions are: crystallization at 180-200° C. for 0.5-72 h and pressure of 0.01-7 MPa, preferably pressure of 0.1-3 MPa.

[0016] Furthermore, the drying conditions are: temperature of 50-120° C. and time of 3-12 h.

[0017] The second aspect of the present invention also provides a molecular sieve prepared by the above method, wherein the molecular sieve is one or more composite molecular sieves selected from ZSM-5, ZSM-11 and SAPO-34.

[0018] Furthermore, the molecular sieve is spherical in shape, with a rough outer surface, and walnut-shaped grains grow on the spherical outer surface. The spherical grain size is 5-10 microns, and the walnut-shaped grain size is 0.4-2 microns.

[0019] The third aspect of the present invention provides the molecular sieve described in the second aspect for use in butene cracking reaction.

[0020] Furthermore, the reaction is carried out at a reaction temperature of 500-600° C. and a reaction pressure of 0.01-0.3 MPa.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] The method provided by the present invention realizes the integration of molecular sieve aging and crystallization. First, the initial gel of the reaction mixture is prepared and sent to the ultra-gravity aging and crystallization integrated device, which is first pre-mixed and circulated, and then directly non-circulated crystallized to realize the aging and crystallization integrated process. The integrated device uses the ultra-gravity aging and crystallization integrated device in both the molecular sieve aging and crystallization processes. The integrated device is simple to operate and has stable performance.

[0023] The molecular sieve prepared by the method provided by the invention has a spherical morphology, a rough outer surface, and walnut-shaped grains growing on the spherical outer surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 is the XRD pattern of the molecular sieve of Example 1;

[0025] Figure 2 This is the SEM image of the molecular sieve of Example 1;

[0026] Figure 3 This is the SEM image of the molecular sieve of Example 2;

[0027] Figure 4 This is the XRD diagram of the molecular sieve of Example 4. DETAILED DESCRIPTION

[0028] The following examples will further illustrate the molecular sieve synthesis method provided by the present invention, but the protection scope of the present invention is not limited to these examples.

[0029] In the present invention, the scanning electron microscope (SEM) images of the samples were taken on a Hitachi S-4800II scanning electron microscope.

[0030] In the present invention, the XRD test conditions are as follows: the molecular sieve crystal phase analysis is performed using a Japanese Rigaku-Ultima X-ray diffractometer, CuKα radiation, wavelength λ=0.15432nm, the X-ray diffraction pattern scanning range 2θ is 5-50°, and the scanning speed is 10° / min.

[0031] Example 1

[0032] The silicon source, aluminum source, template T and water are mixed to obtain an initial gel, and the initial gel is fed through the feeding system of the supergravity integrated device at a feeding rate of 50 ml / min. Among them, the silicon source is silica sol, the aluminum source is aluminum sulfate, the template T is TPABr, and the molar ratio of the silicon source, aluminum source, template and water is H2O / SiO2=20; Si / Al=50, T / SiO2=0.05. The initial gel is circulated in the reaction system of the supergravity aging crystallization integrated device, wherein the supergravity speed is 1500rpm and the time is 5h. Through this process, the gel is evenly mixed, and the raw materials after the premixing cycle are directly crystallized. After 30 minutes of supergravity non-cyclic crystallization at 200°C and pressure of 0.5MPa, the reaction is stopped. After cooling to room temperature, the integrated device is removed through the discharging system, the product is washed and centrifuged 3 times, and dried at 80°C for 12h. After drying, a zeolite molecular sieve is obtained. XRD diagram is shown in Figure 1 , is ZSM-5 molecular sieve. SEM photo see Figure 2 , spherical, with a rough outer surface, and walnut-shaped grains growing on the spherical outer surface, wherein the spherical particle size is 5 microns, and the size of the walnut-shaped grains is 0.4-0.7 microns.

[0033] Example 2

[0034] The silicon source, aluminum source, template T and water are mixed to obtain an initial gel, which is fed through the feeding system of the supergravity integrated device at a feeding rate of 50 ml / min. Among them, the silicon source is silica sol, the aluminum source is aluminum sulfate, the template T is TPABr, and the molar ratio of the silicon source, aluminum source, template T and water is H2O / SiO2=30; Si / Al=50, T / SiO2=0.02. The initial gel is circulated in the reaction system of the supergravity aging crystallization integrated device, wherein the supergravity speed is 1600rpm and the time is 48h. Through this process, the gel is uniformly mixed, and the raw materials after the premixing cycle are directly crystallized. The supergravity non-cyclic crystallization is carried out at 180°C and 0.7MPa under pressure for 4h, and the reaction is stopped. After cooling to room temperature, the integrated device is removed through the discharging system, the product is washed and centrifuged 3 times, and dried at 80°C for 12h. After drying, a zeolite molecular sieve is obtained. XRD is similar to that of Example 1, and it is ZSM-5 molecular sieve. SEM photos are shown in Figure 3 , spherical, with a rough outer surface, and walnut-shaped grains growing on the spherical outer surface, wherein the spherical particle size is 6 microns, and the size of the walnut-shaped grains is 0.5-0.7 microns.

[0035] Example 3

[0036] The silicon source, aluminum source, template T and water are mixed to obtain an initial gel, and the initial gel is fed through the feeding system of the supergravity integrated device at a feeding rate of 100 ml / min. Wherein, the silicon source is silica sol, the aluminum source is aluminum sulfate, the template T is TPABr, and the molar ratio of the silicon source, aluminum source, template and water is H2O / SiO2=50; Si / Al=1000, T / SiO2=0.1. The initial gel is circulated in the reaction system of the supergravity aging crystallization integrated device, wherein the supergravity speed is 2000 rpm and the time is 48 hours. Through this process, the gel is evenly mixed, and the raw materials after the premixing cycle are directly crystallized. After 30 minutes of supergravity non-cyclic crystallization at 150°C and pressure of 0.5 MPa, the reaction is stopped. After cooling to room temperature, the integrated device is removed through the discharging system, the product is washed and centrifuged 3 times, and dried at 80°C for 12 hours. After drying, a zeolite molecular sieve is obtained. XRD diagram is the same as Example 1 Figure 1 The SEM photo is similar to that of Example 1, showing a spherical shape with a rough outer surface, and walnut-shaped grains growing on the outer surface of the sphere, wherein the spherical particle size is 5 microns, and the size of the walnut-shaped grains is 0.5-0.7 microns.

[0037] Example 4

[0038] The silicon source, aluminum source, template T, phosphorus source and water are mixed to obtain the initial gel, which is fed through the feeding system of the supergravity integrated device at a feeding rate of 50 ml / min. Among them, the silicon source is silica sol, the aluminum source is aluminum sulfate, the template T is TEAOH, and the phosphorus source is phosphoric acid. The molar ratio of silicon source, aluminum source, template, phosphorus source and water is Al2O3: 2P2O5: 0.6SiO2: 0.2TEAOH: 140H2O. The initial gel is circulated in the reaction system of the supergravity aging crystallization integrated device, wherein the supergravity speed is 1600rpm and the time is 24h. Through this process, the gel is uniformly mixed, and the raw materials after the premixing cycle are directly crystallized. After supergravity non-cyclic crystallization at 190°C and pressure 1MPa for 60min, the reaction is stopped. After cooling to room temperature, the integrated device is removed through the discharging system, the product is washed and centrifuged 3 times, and dried at 80°C for 12h to obtain the final SAPO-34 product. The photo is similar to Example 1, which is spherical with a rough outer surface and walnut-shaped grains growing on the spherical outer surface. The spherical particle size is 5 microns, and the size of the walnut-shaped grains is 0.6-1 micron.

[0039] Example 5

[0040] The walnut-shaped ZSM-5 molecular sieve aggregate prepared in Example 1 was applied to butene cracking reaction, with a catalyst dosage of 0.6 g, a reaction temperature of 550° C., a reaction pressure of 0.04 MPa, and a reaction time of 6 hours. The butene conversion rate was 80%, and the propylene selectivity was 45%.

[0041] Comparative Example 1

[0042] According to the method of Example 1, the rotation speed was changed to 4000 rpm, and the sample obtained was a spherical ZSM-5 molecular sieve with a morphology as shown in Figure 4 The particle size is 0.5-1 micron, and no walnut-shaped molecular sieve is produced.

[0043] The spherical ZSM-5 molecular sieve aggregates prepared in Comparative Example 1 were used in a butene cracking reaction, with a catalyst dosage of 0.6 g, a reaction temperature of 550° C., a reaction pressure of 0.04 MPa, and a reaction time of 6 hours. The butene conversion rate was 60%, and the propylene selectivity was 15%.

[0044] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a molecular sieve, comprising the following steps: Prepare an initial gel, including a silicon source, an aluminum source, a template agent T and water, and an optional phosphorus source, send it into a high-gravity aging crystallization integrated device for premixing and circulation, then directly crystallize it, and dry it after leaving the device to prepare a molecular sieve; The crystallization is directly carried out as non-cyclic crystallization after premixing cycle in the integrated device for high gravity aging crystallization.

2. The method according to claim 1, characterized in that The ultra-gravity aging crystallization integrated device comprises a feeding system, a reaction system and a discharging system.

3. The method according to claim 2, characterized in that The initial gel is fed through the feeding system of the integrated device for high gravity aging and crystallization, and then undergoes premixing cycle reaction and crystallization in the reaction system in sequence, and then exits the device through the discharging system.

4. The method according to claim 1, characterized in that The template agent T is at least one of tetrapropylammonium bromide, tetrapropylammonium hydroxide, tetramethylammonium bromide, tetraethylammonium bromide, tetrabutylammonium bromide, tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, n-propylamine, n-butylamine, n-hexylamine, methylamine, ethylamine, ethylenediamine, diethanolamine, hexamethylene diisocyanate, hexamethylenediamine, hexamethylenetetramine and derivatives thereof; the silicon source is at least one of silica sol, tetraethyl orthosilicate and silicate; the aluminum source is at least one of aluminum sulfate, aluminum isopropoxide and aluminate; and the phosphorus source is at least one of phosphoric acid or phosphates.

5. The method according to claim 1, characterized in that The molar ratio of the silicon source, aluminum source, template T, phosphorus source and water is H2O / SiO2=10-500; Si / Al=20-∞, T / SiO2=0.01-20, P / SiO2=0-50.

6. The method according to claim 1, characterized in that During the premixing cycle in which the initial gel is fed into the reaction system through the integrated device for high-gravity aging and crystallization, the high-gravity speed is maintained at 1000-2500 rpm for 5 minutes to 48 hours.

7. The method according to claim 1, characterized in that The crystallization conditions are: crystallization at 180-200° C. for 0.5-72 h and pressure of 0.01-7 MPa, preferably, pressure of 0.1-3 MPa.

8. The molecular sieve prepared by the method according to any one of claims 1 to 7.

9. The molecular sieve according to claim 8, characterized in that: The molecular sieve is one or more composite molecular sieves selected from ZSM-5, ZSM-11 and SAPO-34.

10. The molecular sieve according to claim 8, characterized in that: The molecular sieve is spherical in shape, with a rough outer surface, and walnut-shaped crystals growing on the spherical outer surface. The spherical particle size is 5-10 microns, and the particle size of the walnut-shaped crystals is 0.4-2 microns.

Citation Information

Patent Citations

  • Preparation method of nano-ZSM-5 molecular sieve

    CN101643219A

  • Preparation method for mesoporous ZSM-5 zeolite molecular sieve

    CN102826569A

  • Preparation method of ZSM-5 molecular sieve

    CN103183358B